2007
DOI: 10.4038/jnsfsr.v35i2.3676
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of impact of climate change on productivity of tea (Camellia sinensis L.) plantations in Sri Lanka

Abstract: A study was undertaken to assess impact of climate change on productivity of tea lands in Sri Lanka. Findings of the study showed that tea cultivations at low and mid elevations are more vulnerable to adverse impacts of climate change than those at high elevations. The optimum temperature for tea cultivation was found to be about 22 °C. The study also indicated that reduction of monthly rainfall by 100 mm could reduce the productivity by 30 -80 kg of 'made' tea ha" 1 . In different tea growing regions, the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 5 publications
1
77
0
1
Order By: Relevance
“…and high (1380 m a.s.l.) elevations in Sri Lanka, Wijeratne et al (2007a) showed that an increase in C a from the present ambient level of 370 μmol mol -1 to 600 μmol mol -1 increased tea yields by 33 and 37% at the high and low elevations, respectively. Increases in both N sh and W sh contributed to these increases in yield.…”
Section: Effect Of Global Climate Changes On Tea Productionmentioning
confidence: 77%
See 1 more Smart Citation
“…and high (1380 m a.s.l.) elevations in Sri Lanka, Wijeratne et al (2007a) showed that an increase in C a from the present ambient level of 370 μmol mol -1 to 600 μmol mol -1 increased tea yields by 33 and 37% at the high and low elevations, respectively. Increases in both N sh and W sh contributed to these increases in yield.…”
Section: Effect Of Global Climate Changes On Tea Productionmentioning
confidence: 77%
“…The intensity of these climate impacts on tea production will likely vary across the major tea growing regions, in low-, up-and mid-country areas (Wijeratne et al 2007a). Prior research has also identified eight agro-ecological tea-growing areas which are most vulnerable to climate change (Wijeratne and Chandrapala 2013).…”
Section: Effect Of Global Climate Changes On Tea Productionmentioning
confidence: 99%
“…and high (1380 m a.s.l.) elevations in Sri Lanka, Wijeratne et al (2007b) showed that an increase of C a from the present ambient level of 370 µmol mol -1 to 600 µmol mol -1 (which is predicted to occur during the middle of this century) increased tea yields in Sri Lanka by 33 and 37% at high and low elevations, respectively. The long-term averages of maximum/minimum temperatures at the high and low elevations were 20.5 o / 11.5 o C and 32.0 o /22.9 o C, respectively.…”
Section: Response Of Tea To Climate Changementioning
confidence: 98%
“…The study of Wijeratne et al (2007b) also identified several climate change-induced variables which would have negative impacts on tea yields and thereby reduce the potential yield gains due to increasing C a . Particularly, a quadratic relationship, with the optimum around 22 o C, was found between monthly tea yield and monthly mean T a during 'wet' periods.…”
Section: Response Of Tea To Climate Changementioning
confidence: 99%
“…The change and variability in climate patterns over recent decades is not only affecting annual crops but have already impacted perennial cash crops, such as coffee and Cocoa (Craparo et al, 2015), wine and grape Vitivin, 2013;Boyer et al, 2016) and tea (Wijeratne & Anandacumaraswamy, 2007).…”
Section: Impacts Of Climate Change In Tropical Countriesmentioning
confidence: 99%